Greater horseshoe bat (Rhinolophus ferrumequinum) ultrasound calls outside a nursery roost indicate social interaction not light sampling. (2016) - (Writer on bats), Andrews, Margaret M; (Writer on bats), Andrews, Peter T
No abstract available